Regurgitasi Mitral Kronik: Waktu Intervensi yang Optimal - Estu Rudiktyo; Amiliana M. Soesanto (Jurnal Kardiologi Indonesia, 2015)
Chronic mitral regurgitation is commonly encountered valve disease. In this disease, there is volume overload on the left ventricle leading to left ventricle dilatation and dysfuction. Surgical or percutaneous intervention can improve prognosis, however optimal timing of intervention still controversial. In the past, timing of intervention was based solely on symptoms and left ventricle function. There have been recent advances in our knowledge, diagnosis, and treatment of mitral regurgitation. All of these advances have provided an incentive to change the indication for timing of operations in patients with mitral regurgitation, setting a new paradigm of an early operation before the onset of ventricular dysfunction. In this article we will outline these newer advances and provide recommendations regarding optimal timing of intervention for mitral regurgitation.